Test for azacyclonol in some acute psychotic reactions - Jerí, Raúl (1957)
The first results of a test with some acute psychotic azacyclonol react are presented in this communication. The azacyclonol is one of the most recent treatment of psychosis drugs. Has an action on the central nervous system, probably by inhibiting serotonin and therefore produces similar effects to reserpine and chlorpromazine. The main activity is to override the clinical and bio-electrical disturbances produced by alucinóqenos drugs (LSD and mescaline). In various toxic psychosis and acute schizophrenic reactions has done away with mental disorders, sometimes in an extremely short time. Certain psychotic reactions have been referred during the first intravenous injection of the preparation. In this work, the first thing you do in the country, azacyclonol used intravenously and orally in 11 cases, 5, suffered from paranoid schizophrenia, paranoid psychosis 3, 2 and 1 toxic psychosis obsessive reaction involution. All were recent cases, except one. The observation time varied between 3-40 days, the average dose was 100 mgs. day and the results have been good in one, fair in 3 and zero in 7 cases. However, the series is too small and the observation time too short to draw conclusions. The azacyclonol not produce electro-encephalographic changes in four patients studied, using cortical and basal electrodes, where the research was done before and two hours after intravenous injection of 100-200 mgs.